Acinic cell carcinoma, papillary-cystic variant: a rare case diagnosed in fine needle aspiration cytology - M. Patel, Mandakini; N. Gamit, Bhavna; M. Patel, Sharmistha; I. Patel, Mubin; S. Gandhi, Shivangi (International Journal of Research in Medical Sciences, 2018)
Acinic Cell Carcinoma is a rarest malignant epithelial neoplasm arising from pleuripotent stem cells. ACC constitute 6% of all salivary gland tumor. Most common site is parotid. It is slowly growing tumor with female preponderance most commonly occur during fifth and sixth decades of life. Diagnosis by imaging study are complex, but USG is helpful in evaluating tumor. We are presenting a 9year female, complaint of a painless, freely movable, atraumatic swelling on left cheek measuring 2x1cm2, slowly enlarging since, 8 months. FNAC was performed from the swelling and routine stain (H and E, MGG, Pap) and special stain (PAS) was performed. On cytological smears, overall findings are suggestive of papillary-cystic variant of ACC which is difficult to diagnosed in cytology. PAS stain showed positivity for both intra-cytoplasmic granules and extra-cellular secretions. ACC is a slowly growing multi-potent malignant salivary gland tumor. Management is with surgery.